Occlusal Contact Recordings in Static and Functional Occlusion: Description of an Observational Method - Philip L. Millstein; Edward W. Merrill (Journal of Dentistry And Oral Implants, 2022)
This methods paper describes a standardized approach for recording occlusal contacts in static and functional states. It outlines instrumentation, calibration, and interpretation steps aimed at improving reproducibility in clinical dentistry.
Keywords: occlusion